PHARMACOGENETICS: INTERINDIVIDUAL DIFFERENCES IN RESPONSE TO DRUG- AN OVERVIEW - SACHDEV YADAV (International Journal of Pharma and Bio Sciences, 2010)
The field of pharmacogenetics was stimulated in 1970s when Vesell and Colleagues demonstrated that plasma half-lives of many drugs are less divergent among monozygotic twin pairs than among dizygotic twin pairs. This paper reviews about various study methods of pharmacogentics such as unimodal , bimodal studies and trimodal studies.